The influence of extreme thermal stress on the physiological and psychological characteristics of young women who sporadically use the sauna: practical implications for the safe use of the sauna - Podstawski, Robert; Borysławski, Krzysztof; Józefacka, Natalia Maja; Snarska, Jadwiga; Hinca, Bożena; Biernat, Elżbieta; Podstawska, Anna (Frontiers in Public Health, 2024)
Background Many individuals who use the sauna at a temperature of 120°C of higher are not aware of the negative consequences of extreme thermal stress. Despite extensive research into sauna use, the impact of extreme thermal stress on the physiological and psychological characteristics of sauna users have not been examined to date. Aim The aim was to determine the effect of 20 min sauna sessions with a temperature of 80°C and 120°C on the physiological and psychological characteristics of women who sporadically visit the sauna. Methods The study was conducted on 22 full-time female university students. Physical activity (PA) levels were evaluated with the Polish short version of the International Physical Activity Questionnaire (IPAQ). Anthropometric characteristics were measured before the first sauna session by the InBody270 body composition analyzer. Physiological parameters, including heart, energy expenditure, physical effort, and blood pressure (systolic blood pressure – SBP, and diastolic blood pressure – DBP), were assessed indirectly using Polar V800 heart rate monitors and the Omron M6 Comfort blood pressure monitor. The participants’ wellbeing was assessed with the Profile of Mood States (POMS) questionnaire. The presence of significant correlations between heat exhaustion and heat stress variables and syncope during the second sauna session was examined with the use of classification and regression trees (CRT) and the cross-validation technique. Results Twenty-minute sauna sessions with a temperature of 80°C and 120°C induced a significant (p < 0.001) decrease in the values of SBP (excluding the temperature of 120°C), DBP, and body mass, as well as a significant increase in HR and forehead temperature. Exposure to a temperature of 80°C led to a significant (p < 0.001) increase in vigor with a simultaneous decrease in tension, depression, anger, fatigue, and confusion. In turn, sauna bathing at a temperature of 120°C had an opposite effect on the above mood parameters. Vomiting and confusion were the main predictors of syncope that occurred in some of the surveyed women. Conclusion Excessive air temperature can induce symptoms characteristic of heat exhaustion and heat stress nausea, heavy sweating, fast weak or strong HR, high body temperature, and confusion. Therefore, sauna bathing at a temperature of 80°C can be recommended to women who sporadically use the sauna, whereas exposure to a temperature of 120°C is not advised in this group of sauna users. The present findings provide highly valuable inputs for managing wellness and SPA centers.